Robust Provable Data Possession Protocol - Chao Feng; Yixian Yang; Jing Zhang; Yang Xin (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Provable data possession (PDP) is a technique for ensuring the validity of data in storage outsourcing. The main issue is how to frequently, efficiently verify that an untrusted server is correctly storing its client’s outsourced data. In this paper, we introduce a robust provable data possession protocol that allows a client that has stored he/her data at an untrusted server to verify the validity of data without retrieving it. The client preprocesses the data and sends it to an untrusted server for storage, while keeping a small amount of meta-data. Then the client generates probabilistic proofs of possession by sampling a random set of blocks from the server to prove that the stored data has not been tampered with or deleted, which drastically reduces I/O costs. In additions, by means of the careful integration of online codes and PDP (O-PDP), the scheme can recovers a small amount of the file, once it has been deleted. Finally, we conduct an experimental evaluation to study the performance, and robustness of O-PDP.